PENGGUNAAN MODEL PROJECT BASED LEARNING DENGAN METODE PEER TUTORING DALAM PEMBELAJARAN HUKUM ARCHIMEDES - Uada, Putri Angel; Poluakan, Cosmas; Rampengan, Alfrie M.; Taunaumang, Heindrich; Mandang , Theresje; Tumalun, Nicky K. (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2025)
This article aims to determine the effect of using the project-based learning model with the peer tutoring method in teaching Archimedes' principle in physics. This research was conducted at SMA Negeri 1 Tombatu using a quantitative research design with a one-group pre-test post-test design. The use of the project-based learning model with the peer tutoring method enabled students to understand the material taught, based on student learning outcomes, namely the pre-test results showed that the average score of students was 35.83 and increased to 84 in the post-test results. Thus, it can be concluded that the use of the project-based learning model with the peer tutoring method has a significant effect on student learning outcomes in physics learning on Archimedes' principle.